Megan Bartholomew: capstone - Bartholomew, Megan, artist (Colorado State University. Libraries, 2024)
The artist's statement: My work centers around themes of environmentalism and escapism. The imagery I use highlights features of Mother Nature while also contrasting the inorganic forms of manmade structures. I use shadows in my work to bring up discussions of silent pollution and the fragility of nature in these conditions. Pollution has been a topic of worry for decades, with lists of environmental issues only growing. I have always held a feeling of uncertainty for the quality of our future, this emotional escapism also presents itself within the lack of clarity in my work. I often start by taking bokeh-style photographs of my surroundings including skyscapes, skylines and local foliage. I tend to focus on high-contrast forms and vibrant hues to show off the limitless palette of the outdoors. Using soft mediums to depict this imagery feels the most natural to me, as I can smear the pigment like mud or crumble it into sand. I enjoy illustrating on different kinds of fabric such as denim and wool felt, further softening the imagery and bringing life back into once 2D photographs. Reclaimed materials are also an important part of my work, reinforcing my commitment to sustainability and reminding my viewers to think about the impact of single-use materials.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing